Rare bird documentation form for Northern Goshawk at Kent Park, 1983 - Bendorf, Carl J.et al (1983)
Rare bird documentation form for a Northern Goshawk at Kent Park in Johnson County, IA on December 17, 1983. Epson - sheet feed